Exploring the innovation landscape of bamboo fiber technologies from global patent data perspective - Minghan, Sun; Xiuzhu, Zhu; Man, Jiang (Cellulose (London), 2020)
With the global popularity of the concept of green and sustainable development, bamboo fiber technology has made great advances and found its way into several important materials applications. This study attempts to analyze the bamboo fiber technology from a patent perspective, hoping to help enterprises and R&D personnels better grasp the technology development trend and evolution path. Because the current patent analysis methods can not achieve the above objectives well, this paper proposes a new method of clustering and identifying sub-clusters by constructing bamboo fiber patent citation network and patent-international patent classification two mode network. Moreover, this paper uses natural language processing and main path analysis to perform subject word analysis and key technology identification on these technological sub-clusters, respectively. The analysis process and method in this study also have implications for patent analysis in technological fields such as graphene or carbon fiber.